Pengembangan Sistem Informasi (Website & Aplikasi) Desa Sumberbrantas, Kota Batu untuk Peningkatan Kepariwisataan & Kesejahteraan Masyarakat - Muhaimin Achsin; Rita Parmawati; Johan Wahyudi; Zaqlul Iqbal (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The development of a village information system must be done because it is mandated by Law no. 6 of 2014 concerning villages, especially article 86. In article 86 point (2), it states that